Effects of dietary lipid level and vegetable oil on fatty acid metabolism in Atlantic salmon (Salmo salar L.) over the whole production cycle - Tocher, Douglas R; Bell, J Gordon; McGhee, Fiona; Dick, James R; Fonseca-Madrigal, Jorge (Springer, 2003)
Changes in fatty acid metabolism in Atlantic salmon (Salmo salar) induced by vegetable oil (VO) replacement of fish oil (FO) and high dietary oil in aquaculture diets can have negative impacts on the nutritional quality of the product for the human consumer, including altered flesh fatty acid composition and lipid content. A dietary trial was designed to investigate the twin problems of FO replacement and high energy diets in salmon throughout the entire production cycle. Salmon were grown from first feeding to around 2 kg on diets in which FO was completely replaced by a 1:1 blend of linseed and rapeseed oils at low (14-17%) and high (25-35%) dietary oil levels. This paper reports specifically on the influence of diet on various aspects of fatty acid metabolism. Fatty acid compositions of liver, intestinal tissue and gill were altered by the diets with increased proportions of C18 polyunsaturated fatty acids and decreased proportions of n-3 highly unsaturated fatty acids (HUFA) in fish fed VO compared to fish fed FO. HUFA synthesis in hepatocytes and enterocytes was significantly higher in fish fed VO, whereas β-oxidation was unaltered by either dietary oil content or type. Over the entire production cycle, HUFA synthesis in hepatocytes showed a decreasing trend with age interrupted by a large peak in activity at seawater transfer. Gill cell prostaglandin (PG) production showed a possible seasonal trend, with peak activities in winter and low activities in summer and at seawater transfer. PG production in seawater was lower in fish fed the high oil diets with the lowest PG production generally observed in fish fed high VO. The changes in fatty acid metabolism induced by high dietary oil and VO replacement contribute to altered flesh lipid content and fatty acid compositions, and so merit continued investigation to minimize any negative impacts that sustainable, environmentally-friendly and cost-effective aquaculture diets could have in the future. This article was subsequently updated, see revised version on ...